Dual element (CCl) isotope approach to distinguish abiotic reactions of chlorinated methanes by Fe(0) and by Fe(II) on iron minerals at neutral and alkaline pH. (September 2018) - Rodríguez-Fernández, Diana; Heckel, Benjamin; Torrentó, Clara; Meyer, Armin; Elsner, Martin; Hunkeler, Daniel; Soler, Albert; Rosell, Mònica; Domènech, Cristina
Abstract: A dual element CCl isotopic study was performed for assessing chlorinated methanes (CMs) abiotic transformation reactions mediated by iron minerals and Fe(0) to further distinguish them in natural attenuation monitoring or when applying remediation strategies in polluted sites. Isotope fractionation was investigated during carbon tetrachloride (CT) and chloroform (CF) degradation in anoxic batch experiments with Fe(0), with FeCl2 (aq), and with Fe-bearing minerals (magnetite, Mag and pyrite, Py) amended with FeCl2 (aq), at two different pH values (7 and 12) representative of field and remediation conditions. At pH 7, only CT batches with Fe(0) and Py underwent degradation and CF accumulation evidenced hydrogenolysis. With Py, thiolytic reduction was revealed by CS2 yield and is a likely reason for different Λ value (Δδ 13 C/Δδ 37 Cl) comparing with Fe(0) experiments at pH 7 (2.9 ± 0.5 and 6.1 ± 0.5, respectively). At pH 12, all CT experiments showed degradation to CF, again with significant differences in Λ values between Fe(0) (5.8 ± 0.4) and Fe-bearing minerals (Mag, 2 ± 1, and Py, 3.7 ± 0.9), probably evidencing other parallel pathways (hydrolytic and thiolytic reduction). Variation of pH did not significantly affect the Λ values of CT degradation by Fe(0) nor Py. CF degradation by Fe(0) at pH 12 showed a Λ (8 ± 1) similar to that reported at pH 7 (8 ± 2), suggesting CF hydrogenolysis as the main reaction and that CF alkaline hydrolysis (13.0 ± 0.8) was negligible. Our data establish a base for discerning the predominant or combined pathways of CMs natural attenuation or for assessing the effectiveness of remediation strategies using recycled minerals or Fe(0). Graphical abstract: Image 1 Highlights: Carbon tetrachloride (CT) and chloroform (CF) C and Cl isotope fractionation study. CT and CF abiotic reactions with Fe(0), FeCl2, pyrite and magnetite were assessed. Unlike at pH 12, at pH 7 only CT degradation by Fe(0) and pyrite was detected. Different CCl plots for CT hydrogenolysis and CT hydrolytic or thiolytic reduction. Reactions with Fe(0) and pyrite showed similar Λ for each compound regardless pH.